The hammer of Eden : a novel - Follett, Ken (New York : Crown Publishers, 1998)
A group of eco-terrorists threaten to start an earthquake and destroy San Francisco unless the government abandons plans to create a dam. They are ignored until the earth trembles and FBI agent Judy Maddox discovers that the technology for a man-made earthquake is available. At which point a race against time gets underway.
National College of Business and Arts
Keywords: Terrorists -- Fiction; Action and adventure fiction